2017
DOI: 10.1111/jfpp.13217
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth (Amaranthus spp .) starch isolation, characterization, and utilization in development of clear edible films

Abstract: The aim of this study was to analyze the isolated starches for physico‐chemical, structural, and morphological characteristics and to see amaranth starch efficacy in formation of edible films. All the amaranth cultivars have presented purity in range from 99.54 to 99.74% (db). Granules of starch were found small in size ranged from 1.182 to 1.431 µm (PSA). Granules of Amaranth starches showed tightly packed, angular, and polygonal shape (SEM). X‐ray diffraction analysis indicating A type crystalline structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
18
2
Order By: Relevance
“…The film formation process was standardized for obtaining polymeric edible film of desired quality attributes according to Chandla et al, (2017a) with little modification as per variation in starch source. After carrying out the primary trials, separately for amaranth starch, buckwheat starch and corn starch, the edible biodegradable film formation process was standardized.…”
Section: (4) Edible Films Preparation Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The film formation process was standardized for obtaining polymeric edible film of desired quality attributes according to Chandla et al, (2017a) with little modification as per variation in starch source. After carrying out the primary trials, separately for amaranth starch, buckwheat starch and corn starch, the edible biodegradable film formation process was standardized.…”
Section: (4) Edible Films Preparation Processmentioning
confidence: 99%
“…red amaranth (Amaranthus tricolor L.) and green amaranth (Amaranthus dubius L.) are tried after quality evaluation to develop feed and food products (Hoang, 2019). Amaranth (Amaranthus hypochondriacus) varieties namely; Annapurna and Durga are grown in many parts of Uttaranchal and Himachal Pradesh by National Bureau of Plant Genetics Resources, (NBPGR), New Delhi, to propagate the amaranth grain cultivation and their utilization in developing value added food products (Chandla et al, 2017a;Rana et al, 2007;Arya and Singh, 2004). Effect of blending of amaranth and bengal gram on the organoleptic quality of wheat based weaning mixes was also investigated (Anand and Malhotra, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the optimized film-forming solution must contain 20% glycerol (4) and the drying conditions must be at 50 ºC with 76.2 % RH (5). Chandla et al (6) isolated starch from amaranth seeds obtaining translucent films with permeability to water vapor (WVP) of 2.03-2.94•10 -10 (g•mm)/(Pa•s•m 2 ) and tensile strength (TS) of 2.3-2.6 MPa. Amaranth proteins have also been reported to have good filmogenic properties (7).…”
Section: Introductionmentioning
confidence: 99%